2019
DOI: 10.1039/c9mt00267g
|View full text |Cite|
|
Sign up to set email alerts
|

Characterising the spatial and temporal brain metal profile in a mouse model of tauopathy

Abstract: A dysregulation in the homeostasis of metals such as copper, iron and zinc is speculated to be involved in the pathogenesis of tauopathies, which includes Alzheimer's disease (AD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 109 publications
0
18
0
Order By: Relevance
“…Drug treatments were performed in a mixed-gender cohort and commenced at 12 months of age. Our previous studies demonstrated that rTg4510 mice have profound behavioral deficits at this age, in addition with a significant accumulation of brain iron [37] and tau pathology, therefore allowing us to examine the use of DFP as a treatment strategy. Mice were housed in Techniplast IVC cages with free access to mouse chow and water.…”
Section: Animalsmentioning
confidence: 99%
“…Drug treatments were performed in a mixed-gender cohort and commenced at 12 months of age. Our previous studies demonstrated that rTg4510 mice have profound behavioral deficits at this age, in addition with a significant accumulation of brain iron [37] and tau pathology, therefore allowing us to examine the use of DFP as a treatment strategy. Mice were housed in Techniplast IVC cages with free access to mouse chow and water.…”
Section: Animalsmentioning
confidence: 99%
“…Drug treatment commenced at 4 months and concluded at the end of 7 months of age. This age was chosen to begin treatment as our previous work demonstrated a significant age-related increase in brain iron levels from 4 months to 7 months of age in rTg4510 compared to age-matched WT mice [46]. Mice were housed in Techniplast IVC cages with free access to mouse chow and water.…”
Section: Animalsmentioning
confidence: 99%
“…The oxidation process slows down or excludes the regular action of the Aβ and tau protein [148]. In animal models of tauopathies, increased iron associated with aging and neurodegeneration has been observed [149]. Indeed, animals with tauopathies treated with the iron chelator deferiprone showed a trend toward improved cognitive function associated with the decrease in brain iron levels and sarkosyl-insoluble tau [150].…”
Section: Ferroptosis In Alzheimer's Diseasementioning
confidence: 99%